Relationships between the activity of neurohormonal systems and intracardiac hemodynamics in patients with heart failure: focus on galectin-3 - V. I. Podzolkov; N. A. Dragomiretsksya; A. V. Kazadaeva; Yu. G. Beliaev; Anastasia V. Tolmacheva (Российский кардиологический журнал, 2022)
The introduction of novel biomarkers necessitates their detailed study in patients with different heart failure (HF) phenotypes as part of a personalized approach to assessing the disease severity and predicting outcomes.Aim. To assessthe activity of following neurohormonal systems: N-terminal probrain natriuretic peptide (NT-proBNP) and galectin-3 in HF with preserved, mildly reduced and reduced ejection fraction (EF).Material and methods.  In 69 patients with NYHA class II-IV HF,  along with a general clinical examination, the level of NT-proBNP and serum galectin-3 was determined by enzyme immunoassay.Results. Patients included in the study were divided into 3 groups: preserved EF (HFpEF) — 23 patients, mildly reduced EF (HFmrEF) — 26 patients, and reduced EF (HFrEF) — 20 patients. In patients with HF, the level of galectin-3 did not directly depend on EF, but was associated with NT-proBNP level as follows: there was a tendency to increase the concentration of galectin-3 in the tertile groups of NT-proBNP. Correlation analysis revealed significant feedback (r=-0,41, p<0,05) between galectin-3 and left ventricular EF only in patients with preserved systolic function. In the same group of HFpEF patients, the maximum values of serum galectin-3 indices were noted, reaching 10,5 [6,5; 14,5] ng/ml.Conclusion. Analysis of neurohormonal activity demonstrated a unidirectional increase in NT-proBNP and galectin-3 in patients with HF, regardless of left ventricular EF, while the maximum values of galetin-3 were observed in patients with HFpEF.